Analysis of Proportional Reasoning Task in Task Series Book MANDIRI Grade VII - Ahmad Lutfi; Mochamad Abdul Basir; Imam Kusmaryono; Dyana Wijayanti (JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to determine the distribution of the percentage of proportional reasoning tasks in the comparison chapter in task series book MANDIRI (Mengasah Kemampuan Diri) Mathematics Grade VII Curriculum 2013, Revised Edition, 2016 Publisher Erlangga, written by Kurniawan. This research is a qualitative research using a descriptive approach. The task data from the book are documented and then analyzed based on indicators from each level of proportional reasoning. The tasks in the comparison chapter consist of two types of tasks, namely multiple choice tasks and essay tasks. There are 225 tasks in the comparison chapter. Based on the results of the study, it was found that the distribution of tasks based on the level of proportional reasoning found that tasks with level 1 (qualitative) were 31 (13.78%), tasks with level 2 (additive) were 22 items (9.78%), tasks with level 3 (pre-multiplicative) were 116 tasks (51.56%), tasks with level 4 (implicit multiplicative) were 24 items (10.67%) and tasks with level 5 (multiplicative) were32 items (14.22%).